Board diversity and financial reporting quality: does firm size matter? - Celina Tan; Muhammad Taufiik (Journal of Contemporary Accounting, 2022)
This study scrutinises how the diversity of a board of directors (BOD) determines the financial reporting quality (FRQ) and how firm size may act in a moderating role. FRQ has two measurments, which are faithful representation and relevance. Faithful representation has one proxy, which is financial restatement. Relevance has two proxies, which are the predictive value and confirmatory value. Moreover, a board’s diversity includes its members’ gender, age, expertise and educational level. The research sample consists of companies listed on the Indonesia Stock Exchange from 2016 to 2020; this produced 377 firms, resulting in 1,885 observations; we used panel data. Boards are homogeneous, except for boards with accounting expertise. Male directors can reduce the potential for financial restatements, but when moderated by firm size, they cannot guarantee the predictive value. Moreover, old directors can also reduce financial misconduct, but unqualified opinions are difficult to obtain when moderated by firm size. Further, a BOD without a member holding a doctoral degree can have a significant adverse effect on financial restatements and agency conflict. Agency conflict is the ultimate result of a negative predictive value. Meanwhile, board expertise boosts the fairness of financial reporting, resulting in obtaining an unqualified opinion and providing a predictive value. The fundamental qualitative characteristics of financial reporting must offer a relevant and faithful representation, while the previous studies employed this separately; this study tackles that gap. The previous research that tested corporate governance on FRQ is still very limited and tends to focus on one topic (e.g. gender), so our research is more comprehensive since BOD diversity was investigated. The FRQ worsens because the BOD is homogeneous. Based on the findings, the FRQ can be improved if there are female directors, younger directors, and directors who hold PhDs serving on the boards. This means that their presence/proportion must increase.